2009
DOI: 10.1021/la802696j
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Technique as a New Approach to Produce Nanostructured Films Containing Phospholipids as Transducers in Sensing Applications

Abstract: Phospholipids are widely used as mimetic systems to exploit interactions involving biological membranes and pharmacological drugs. In this work, the layer-by-layer (LbL) technique was used as a new approach to produce multilayered thin films containing biological phospholipids applied as transducers onto Pt interdigitated electrodes forming sensing units of an electronic tongue system. Low concentrations (nM level) of a phenothiazine compound were detected through impedance spectroscopy. Both negative 1,2-dipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 33 publications
7
71
1
1
Order By: Relevance
“…Therefore, electrostatic interactions between CH 3 -N + (DODAB) and PO 4 − (DPPG) groups appear not to be the main driving force to grow DODAB/DPPG dippingand spray-LbL films. This is in contrast to the results for PAH/DPPG LbL films [38], where stronger interactions between DPPG and PAH leading to larger FTIR spectral changes were found for dipping-LbL films than for the spray-LbL films. For DODAB/DPPG, a shoulder at 1717 cm −1 was observed only for the spray-LbL film, and may be assigned to hydrogen bonds between COO ester groups and glycerol OH groups of adjacent DPPG molecules, according to Dicko et al [45] who reported a shoulder at 1720 cm −1 in the spectrum of a DPPG Langmuir monolayer using polarization-modulated infrared reflection absorption spectroscopy (PM-IRRAS).…”
Section: Monitoring the Growth Of Dodab/dppg Dipping-and Spray-lbl Filmscontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore, electrostatic interactions between CH 3 -N + (DODAB) and PO 4 − (DPPG) groups appear not to be the main driving force to grow DODAB/DPPG dippingand spray-LbL films. This is in contrast to the results for PAH/DPPG LbL films [38], where stronger interactions between DPPG and PAH leading to larger FTIR spectral changes were found for dipping-LbL films than for the spray-LbL films. For DODAB/DPPG, a shoulder at 1717 cm −1 was observed only for the spray-LbL film, and may be assigned to hydrogen bonds between COO ester groups and glycerol OH groups of adjacent DPPG molecules, according to Dicko et al [45] who reported a shoulder at 1720 cm −1 in the spectrum of a DPPG Langmuir monolayer using polarization-modulated infrared reflection absorption spectroscopy (PM-IRRAS).…”
Section: Monitoring the Growth Of Dodab/dppg Dipping-and Spray-lbl Filmscontrasting
confidence: 99%
“…200 nm and 100 nm for dipping-and spray-LbL films, respectively. We concluded that most vesicles were preserved based not only on these AFM images but also on previous evidence from the literature that the vesicles maintain their internal aqueous phase in LbL films [38,52]. Some of the vesicles may nevertheless have been either fused or destroyed by the spraying pressure, as less vesicles are found in the spray-LbL film.…”
Section: The Architecture Of Dipping-and Spray-lbl Filmssupporting
confidence: 54%
See 2 more Smart Citations
“…Of particular relevance is the molecular-level interaction between components which may lead to completely distinctive properties of the final film in comparison to those of the individual components. For instance, Aoki et al [166] immobilized DPPG vesicles onto PAH layers using the LbL technique. FTIR spectroscopy revealed that the interactions between NH 3 + (PAH) and PO 4 − (DPPG) groups are the main driving forces for the PAH/DPPG LbL film growth.…”
Section: Probing Surface Functionalizationmentioning
confidence: 99%